Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^4+2019x^2+2018x+2019\)
\(=x^4-x^3+x^3+2019x^2-x^2+x^2+2019x-x+2019\)
\(=\left(x^4-x^3+2019x^2\right)+\left(x^3-x^2+2019x\right)+\left(x^2-x+2019\right)\)
\(=x^2\left(x^2-x+2019\right)+x\left(x^2-x+2019\right)+\left(x^2-x+2019\right)\)
\(=\left(x^2+x+1\right)\left(x^2-x+2019\right)\)
\(\text{a) }4x^{16}+81=4x^4+36x^2+81-36x^8\)
\(=\left(4x^{16}+36x^8+81\right)-36x^8\)
\(=\left[\left(2x^8\right)^2+2.2x^8.9+9^2\right]+\left(6x^4\right)^2\)
\(=\left(2x^8+9\right)^2-\left(6x^4\right)^2\)
\(=\left(2x^8+9-6x^4\right)\left(2x^8+9+6x^4\right)\)
\(\text{b) }x^4+2018x^2+2017x+2018\)
\(=x^4+2018x^2+2018x-x+2018\)
\(=\left(x^4-x\right)+\left(2018x^2+2018x+2018\right)\)
\(=x\left(x^3-1\right)-2018\left(x^2+x+1\right)\)
\(=x\left(x-1\right)\left(x^2+x+1\right)+2018\left(x^2+x+1\right)\)
\(=\left(x^2-x\right)\left(x^2+x+1\right)+2018\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^2-x+2018\right)\)
Ta có : x4 + 2018x2 + 2017x + 2018
= x4 - x + 2018x2 + 2018x + 2018
= x(x3 - 1) + 2018(x2 + x + 1)
= x(x - 1)(x2 + x + 1) + 2018(x2 + x + 1)
= (x2 + x + 1)(x2 - x + 2018)
Ta có: x=2017
nên x+1=2018
Ta có: \(P=x^{15}-2018x^{14}+2018x^{13}-2018x^{12}+...+2018x^3-2018x^2+2018x-2018\)
\(=x^{15}-\left(x+1\right)\cdot x^{14}+\left(x+1\right)\cdot x^{13}-\left(x+1\right)\cdot x^{12}+...+\left(x+1\right)\cdot x^3-\left(x+1\right)\cdot x^2+\left(x+1\right)\cdot x-\left(x+1\right)\)
\(=x^{15}-x^{15}-x^{14}+x^{14}+x^{13}-x^{13}+...+x^3-x^3+x^2-x^2+x-x-1\)
=-1
F(x)=\(x^7-2018x^6+2018x^5-2018x^4+2018x^3-2018x^2+2018x+1.\)
x=2017=>2018=x+1 thay vào F(x) ta có:
F(x)=x+1=2018
\(A=x^9-2018x^8+2018x^7-2018x^6+2016x^5-2018x^4+2018x^3-2018x^2+2018x-2018\)
\(A=x^9-\left(2017+1\right)x^8+\left(2017+1\right)x^7-...+\left(2017+1\right)x-\left(2017+1\right)\)
\(A=x^9-\left(x+1\right)x^8+\left(x+1\right)x^7-...+\left(x+1\right)x-x-1\)
\(A=x^9-x^9-x^8+x^8+x^7-...+x^2+x-x-1\)
\(A=-1\)
a, =x4-x + 2019x2+2019x+2019
=x(x3-1)+2019(x2+x+1)
=x(x-1)(x2+x+1)+2019(x2+x+1)
=(x2-x+2019)(x2+x+1)
b, =(x-y+y-z)[(x-y)2-(x-y)(y-z)+(y-z)2 ] + (z-x)3
=(x-z)(x2-2xy+y2-xy+xz+y2-yz+y2-2yz+z2) - (x-z)3
=(x-z)(x2-2xy+y2-xy+xz+y2-yz+y2-2yz+z2-x2+2xz-z2)
=(x-z)(-3xy+3y2+3xz-3yz)
=3(x-z)(-xy+y2+xz-yz)
=3(x-z)[(-xy+xz)+(y2-yz)]
=3(x-z)[-x(y-z)+y(y-z)]
=3(y-x)(x-z)(y-z)